Understanding and addressing mathematics anxiety using perspectives from education, psychology and neuroscience. (August 2016) - Buckley, Sarah; Reid, Kate; Goos, Merrilyn; Lipp, Ottmar V; Thomson, Sue
Mathematics anxiety is a significant barrier to mathematical learning. In this article, we propose that state or on-task mathematics anxiety impacts on performance, while trait mathematics anxiety leads to the avoidance of courses and careers involving mathematics. We also demonstrate that integrating perspectives from education, psychology and neuroscience contributes to a greater understanding of mathematics anxiety in its state and trait forms. Research from cognitive psychology and neuroscience illustrates the effect of state mathematics anxiety on performance and research from cognitive, social and clinical psychology, and education can be used to conceptualise the origins of trait mathematics anxiety and its impact on avoidant behaviour. We also show that using this transdisciplinary framework to consider state and trait mathematics anxiety separately makes it possible to identify strategies to reduce the negative effects of mathematics anxiety. Implementation of these strategies among particularly vulnerable groups, such as pre-service teachers, could be beneficial.